2002
DOI: 10.1002/ppul.10146
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma and asthma‐like symptoms in inner‐city elementary schoolchildren

Abstract: American inner-city children are disproportionately affected by asthma. During the 1999-2000 school year, we conducted a survey of 6 Bronx, New York City elementary schools to assess the prevalence of asthma and asthma-like symptoms as reported by parents. Children with probable asthma had symptoms within the last 12 months and parents who indicated that their child had asthma. Children with possible asthma had symptoms within the last 12 months but lacked a diagnosis.Overall, 74% (4,775/6,433) of parents retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 17 publications
4
33
1
Order By: Relevance
“…2,3 Asthma also disproportionately affects African Americans and is present in about 20% of children. 4 In children with SCD, estimates of asthma prevalence are similar to that in children of African descent in the general population, 5,6 making asthma one of the most common co-morbid conditions in SCD.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…2,3 Asthma also disproportionately affects African Americans and is present in about 20% of children. 4 In children with SCD, estimates of asthma prevalence are similar to that in children of African descent in the general population, 5,6 making asthma one of the most common co-morbid conditions in SCD.…”
mentioning
confidence: 74%
“…30 CysLTs are important to asthma pathogenesis, and levels of CysLTs correlate with measures of asthma severity, 31 asthma exacerbations 32 and presence of exercise-induced asthma. 33 LTB 4 and CysLT levels are increased in individuals with SCD when they are well and during vaso-occlusive events. Although LTB 4 levels have a lesser role in the process of asthma, its actions on the activation, migration and adhesion of neutrophils to endothelium suggest that LTB 4 could contribute to the process of vaso-occlusion.…”
Section: Leukotrienes Are Inflammatory Mediators That Are Elevated Anmentioning
confidence: 99%
See 1 more Smart Citation
“…2,6 Asthma is a common chronic disease affecting approximately 15% to 20% of African American children. [7][8][9][10] Previous retrospective studies suggest a relationship between ACS and asthma among children with SCA. We previously reported a 4-fold higher risk of ACS among children with SCA and a prior doctor diagnosis of asthma within a cohort of children with SCA hospitalized for pain.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the gender cofactor, several studies demonstrated lower (total and specific) IgE levels, and a lower incidence of atopy and asthma in females. [12][13][14][15][16] Thus, gender is an important cofactor influencing prevalence and phenotype of IgE-mediated allergic diseases. Taking this into account, we are confident that there are more immune response genes identified that influence IgE or atopy/asthma in a gender-restricted fashion.…”
mentioning
confidence: 99%